2018
DOI: 10.1101/436634
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RegTools: Integrated analysis of genomic and transcriptomic data for the discovery of splice-associated variants in cancer

Abstract: The interpretation of variants in cancer is frequently focused on direct protein coding alterations. However, this analysis strategy excludes somatic mutations in non-coding regions of the genome and even exonic mutations may have unidentified non-coding consequences. Here we present RegTools (www.regtools.org), a free, open-source software package designed to integrate analysis of somatic variant calls from genomic data with splice junctions extracted from transcriptomic data in order to efficiently identify … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 96 publications
1
59
0
1
Order By: Relevance
“…This is an important step as we found a substantial increase in the number of false positive splicing QTL due to allelic bias in read mapping [20]. Exon-exon junctions were extracted using RegTools [60], and clustered and quantified using LeafCutter [20]. As expected, we observed that the number of exon-exon junctions identified in each sample is positively correlated with the sequencing depth in the DICE consortium ( Supplementary Figure 1).…”
Section: Data Processingsupporting
confidence: 55%
“…This is an important step as we found a substantial increase in the number of false positive splicing QTL due to allelic bias in read mapping [20]. Exon-exon junctions were extracted using RegTools [60], and clustered and quantified using LeafCutter [20]. As expected, we observed that the number of exon-exon junctions identified in each sample is positively correlated with the sequencing depth in the DICE consortium ( Supplementary Figure 1).…”
Section: Data Processingsupporting
confidence: 55%
“…Reads spanning the transcription regulatory sequence (TRS) sites of both leader region and the coding genes (S gene, ORF3a, 6, 7a, 8, E, M and N gene) were selected to represent the sgmRNAs. The junction sites were predicted using RegTools junctions extract [19]. The ratio of sgmRNA reads to the viral genomic RNA reads (sgmRNA ratio) was used to estimate the relative transcription activity of SARS-CoV-2.…”
Section: Profiling Of Sub-genomic Messenger Rna (Sgmrnas)mentioning
confidence: 99%
“…in R for each sex and brain-region specific group 75 We employed an adapted protocol 76 on BAM files to extract transcript feature counts from each cortical subregion using regtools 77 and bed_to_junctions from TopHat2 78 .…”
Section: Differential Gene Expression (Dge) Dge Was Calculated Usingmentioning
confidence: 99%